Institutional Childcare: An Overview on the German Market - Grit Muehler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
Institutional early childhood education and care can be funded and delivered in various ways relying on both the public and the private sector. The provision of childcare ranges from public operation to mixed markets with public and private providers to considerably marketised systems with predominantly private providers. One of the countries with a mixed childcare system is Germany where most of the childcare centres are operated by local authorities and non-profit organisations. Using newly available statistical data this paper provides a descriptive overview on the market for childcare in Germany from a providers' perspective. It answers the question if providers differ systematically with regard to centre characteristics, staff employed or the children taken care of. As the results show, the differences in operation affect many dimensions, nevertheless non-religious and for-profit centres on the one hand as well as public and religious centres on the other hand tend show similar characteristics.
More recent version: http://hdl.handle.net/10419/40161
Keywords: L33; H44; J13; 330; institutional childcare; provision; public and private sector; Kinderbetreuung; Organisation; Markt; Deutschland